If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -8x = 10x + 23 Reorder the terms: -1 + -8x = 23 + 10x Solving -1 + -8x = 23 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -1 + -8x + -10x = 23 + 10x + -10x Combine like terms: -8x + -10x = -18x -1 + -18x = 23 + 10x + -10x Combine like terms: 10x + -10x = 0 -1 + -18x = 23 + 0 -1 + -18x = 23 Add '1' to each side of the equation. -1 + 1 + -18x = 23 + 1 Combine like terms: -1 + 1 = 0 0 + -18x = 23 + 1 -18x = 23 + 1 Combine like terms: 23 + 1 = 24 -18x = 24 Divide each side by '-18'. x = -1.333333333 Simplifying x = -1.333333333
| 223-6x=30x+23 | | 5x-26=34 | | 12x-33=7x+2 | | 3x+10=-67-8x | | 2(p-3)=4(p-10) | | 15v^2-19v-10= | | 114-10x=7x+22 | | 4x+10=82-4x | | 2y+5=9 | | 5x-25=20 | | 7+10=115+x | | 110-6x=3x+11 | | -16-5x=12-9x | | 4x+14=77-5x | | -2(5x-3)=-10x+11 | | 3x+25=12x-83 | | 3x+30=5x+14 | | 3x^2-4x+5=0 | | 3x-3=11x-43 | | 2x+29=12x-91 | | x^2-6=0 | | 5x-8=6x-1 | | 0=-4x-32 | | 0=28x^2-12x | | 10m+7n=170 | | 7x^2-16x=18 | | x^2-x=25 | | 14x^2*2x+3=0 | | (ax+c)(bx+d)=(bx+c)(ax+d) | | 10d-8=3d-17-2d | | 7x+16-3x=12-6x-6 | | 6x+y=8 |